Telomerase Reverse Transcriptase Increases Proliferation and Lifespan of Human NK Cells without Immortalization - Streltsova, Maria A. (Biomedicines, 2021)
NK cells are the first line of defense against viruses and malignant cells, and their natural functionality makes these cells a promising candidate for cancer cell therapy. The genetic modifications of NK cells, allowing them to overcome some of their inherent limitations, such as low proliferative potential, can enable their use as a therapeutic product. We demonstrate that hTERT-engineered NK cell cultures maintain a high percentage of cells in the S/G2 phase for an extended time after transduction, while the life span of NK cells is measurably extended. Bulk and clonal NK cell cultures pre-activated in vitro with IL-2 and K562-mbIL21 feeder cells can be transduced with hTERT more efficiently compared with the cells activated with IL-2 alone. Overexpressed hTERT was functionally active in transduced NK cells, which displayed upregulated expression of the activation marker HLA-DR, and decreased expression of the maturation marker CD57 and activating receptor NKp46. Larger numbers of KIR2DL2/3+ cells in hTERT-engineered populations may indicate that NK cells with this phenotype are more susceptible to transduction. The hTERT-modified NK cells demonstrated a high natural cytotoxic response towards K562 cells and stably expressed Ki67, a proliferation marker. Overall, our data show that ectopic hTERT expression in NK cells enhances their activation and proliferation, extends in vitro life span, and can be a useful tool in developing NK-based cancer cell therapies.